An Analysis of Clustering the Decision Support Systems in Logistics for Supply Chain Management - Ahmad Faiz Ghazali; Aishah Suhaimi (Utan Kayu Publishins, 2023)
Decision-making in logistics is becoming increasingly complex task for businesses such as agriculture, food production, and construction, as it requires decisions at the strategic, tactical, and operational levels, as well as consideration of the triple bottom line. Undoubtedly, decision support systems (DSS) played a crucial role in resolving the difficulties related with decision-making in sustainable logistics. The objective of this work is to investigate the status of research in the domain of DSS for logistics, taking sustainability into account. It is of the utmost importance to determine the prospective areas and significance of this research. By doing a bibliometric analysis, the purpose of this study is to illustrate the scientific research on the Decision Support System in Logistics. Using the Scopus database's VOSviewer programme and data analysis tool, the analysis was conducted. From 1985 to 2022, a total of 1091 papers on DSS and logistics connected to consumers were retrieved from the Scopus database. To show the progression of research ideas in this discipline, co-citation analysis and co-word analysis were undertaken. Transportation decision-making, decision analysis, and intelligence algorithm have been identified as the three primary study clusters relevant to the current research interest. This study's findings may assist researchers in comprehending the nature of Decision Support System research pertaining to logistics from around the world and in determining future research directions.